MENINGKATKAN MINAT BELAJAR BAHASA INDONESIA SISWA SD MELALUI MEDIA PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI - Gita Septinauli Sidabutar; Ni Wayan Puji Andari​​; Ni Luh Pegiyanti​​ pegiyanti; Ni Kadek Ayulina Agustini; Ida Bagus Putrayasa; I Nyoman Sudiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of utilizing interactive technology-based learning media to enhance elementary students' interest in learning Bahasa Indonesia. The background of this research is based on the low interest of students in Bahasa Indonesia lessons, often caused by conventional teaching methods that are less engaging. By leveraging technology, the learning process is expected to become more interactive and enjoyable for students. The research method employed is Classroom Action Research (CAR) conducted in two cycles. The subjects of the study are fourth-grade students at S SD 12 Dauh Puri. The interactive learning media used include animations and educational applications such as Wordwall. Data were collected through observation, questionnaires, and documentation, then analyzed descriptively and quantitatively. The results indicate that the use of interactive technology-based learning media can increase students' interest in learning. This is evidenced by an 80% increase in students' learning interest after the implementation of interactive animation media in Bahasa Indonesia lessons. Students became more enthusiastic, active, and motivated in participating in the lessons. The conclusion of this study is that integrating interactive technology-based learning media into Bahasa Indonesia instruction can enhance elementary students' interest in learning. Therefore, it is recommended that educators utilize technology as a teaching aid to create a more engaging and effective learning environment..